The use of plant-derived exosome-like nanoparticles as a delivery system of CRISPR/Cas9-based therapeutics for editing long non-coding RNAs in cancer colon cells - Hillman, Tatiana (Frontiers in Oncology, 2023)
Colon cancer is one of the leading causes of cancer in the United States. Colon cancer develops from the many gene mutations found in the genomes of colon cancer cells. Long non-coding RNAs (lncRNAs) can cause the development and progression of many cancers, including colon cancer. LncRNAs have been and could be corrected through the gene-editing technology of the clustered repeats of the clustered regularly interspaced short palindromic repeats (CRISPR)-associated nuclease 9 (CRISPR/Cas9) system to reduce the proliferation of cancer cells in the colon. However, many current delivery systems for transporting CRISPR/Cas9-based therapeutics in vivo need more safety and efficiency. CRISPR/Cas9-based therapeutics require a safe and effective delivery system to more directly and specifically target cancer cells present in the colon. This review will present pertinent evidence for the increased efficiency and safety of using plant-derived exosome-like nanoparticles as nanocarriers for delivering CRISPR/Cas9-based therapeutics to target colon cancer cells directly.